The effect of metal-cation vacancies on vanadium antimonate surface properties. A theoretical study - Seitz, Hernan (2013)
In this work, we studied the distribution of V and Sb vacancies in the rutile-type vanadium antimonate phase and the influence of these cationic defects on the VSbO4(110) surface properties. We performed density functional theory (DFT) calculations to compute the energy stability of bulk supercells with different geometrical arrangements of the metal-cation-deficient sites. Then, we built a model of the nonstoichiometric VSbO4(110) surface, which exhibited an extra O layer and isolated V cations—V atoms surrounded by Sb ions—that could act as Lewis acid sites. The density of states (DOS) plot of this surface showed contributions of O(2p) states, coming from surface O atoms nearest-neighbor of a V vacancy, and V(3d) states near the Fermi level. We also studied the influence of cation-vacancies in the formation of Brønsted acid sites.